(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To determine the current situation in allergic rhinitis (AR) caused by cotton dust allergen in workers at X20 Garment Company- General Department of Defense Industry. Subjects and methods: A cross-sectional descriptive study from August 2015 to August 2016. Results: The rate of AR due to cotton dust allergen is 13.9%; the majority of women (78.4%); 73.1% of patients had a personal history of allergies; mean age 11.86 ± 5.54.); The risk of AR of direct workers is 2.03 times higher than that of indirect workers. The functional symptoms are mainly at moderate and mild levels, especially severe and moderate sneezing symptoms account for the highest (43.8% and 42.7%); most patients have moderate (42.7%) and mild (44.9%) nasal mucosal lesions; patients with hypertrophy inferior turbinate were mainly mild (50.6%), no patient had severe hypertrophy. None of the patients had negative skin prick test results; the percentage of patients with positive skin prick test results 2(+) and 3(+) accounted for the majority, 41.6% and 32.6% respectively. Conclusion: AR caused by cotton dust allergen has all the characteristics of AR in general; the rate of AR by cotton dust allergen is 13.9%; The group of direct workers has a much higher rate of AR than the group of indirect workers; the symptoms, skin test of patients with AR caused by cotton dust allergen are mainly mild and moderate.